Migration, gender and social justice : Perspectives on human insecurity - Gasper, Des; Handmaker, Jeff; Bergh, Sylvia I.; Truong, Thanh-Dam (Hexagon Series on Human and Environmental Security and Peace, 2014)
This book is the product of a collaborative effort involving partners from Africa, Asia, Europe and Latin America who were funded by the International Development Research Centre Programme on Women and Migration (2006-2011). The International Institute of Social Studies at Erasmus University Rotterdam spearheaded a project intended to distill and refine the research findings, connecting them to broader literatures and interdisciplinary themes. The book examines commonalities and differences in the operation of various structures of power (gender, class, race/ethnicity, generation) and their interactions within the institutional domains of intra-national and especially inter-national migration that produce context-specific forms of social injustice. Additional contributions have been included so as to cover issues of legal liminality and how the social construction of not only femininity but also masculinity affects all migrants and all women. The resulting set of 19 detailed, interconnected case studies makes a valuable contribution to reorienting our perceptions and values in the discussions and decision-making concerning migration, and to raising awareness of key issues in migrants' rights.  All chapters were anonymously peer-reviewed. This book resulted from a series of projects funded by the International Development Research Centre (IDRC), Canada.